DESIGN OF HIGH-SPEED IGBT DEVICE - I. Yu. Lovshenko; V. R. Stempitsky; A. S. Turtsevich; I. .. Shelibak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Results of the investigation of IGBT manufacturing technology parameters influence on its dynamic features are presented. The important role of impurities concentration in various parts of IGBT structure (concentration level in the emitter of the bipolar transistor as apart of the IGBT structure, implantation dose in the MOS channel, the energy of ions implanted in the base of the bipolar transistor) was shown. These effects are discussed with the standpoint of dynamic characteristics of charge carriers. It was discovered that the level of impurity concentration in the emitter does not affect on the device dynamic features and reveals only small influence from the level of impurity concentration in the base. More effect is determined by the dose and energy of implanted ions under the doping of the MOS channel: the two-time dose increasing leads 20 % decreasing of switch on and switch off times of IGBT and the 20 % increasing of the ion energy leads to 25 % increasing of output impulse duration.